(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Osmotic demyelination syndrome is a rare neurological disease resulting in cerebral apoptosis and loss of myelin due to osmotic stress. Based on anatomical localization and pathological attributes, ODS can be categorized as Central Pontine Myelinolysis (CPM) and Extrapontine Myelinolysis (EPM). It has a biphasic course, with first phase reflecting electrolyte imbalance and the second with pontine dysfunction, impaired vigilance and movement disorders. In an autopsy-based study, a prevalence rate of 0.25–0.5% was seen in the general population and 10% in patients undergoing liver transplantation. Being a rare disease with variable, but preventable outcome, the present case was managed with Ayurvedic oral medication and Panchakarma therapy with an aim to improve the quality of life. In Ayurvedic perspective, Vata kshaya lakshanas occur during the phase of hyponatremia and further correction of this leads to disruption of osmolality (Kapha pitta accumulation) resulting in Avarana of Vata. This may be the reason for demyelination and localisation of Vata in Sira and Snayu leading to Sira snayu shoshana on both halves of the body resulting in Sarvangaroga (full body afflicted with Vata). Thus Avaranahara, Srotosodhana and Vatanulomana principles were adopted. An improvement in Barthel index and modified rankin scale were observed after a course of treatment for 30 days.